Erosion infiltration technique': A novel alternative for masking enamel white spot lesion - Praveen Muthuvel; Aarthi Ganapathy; Mohan Kumar Subramaniam; Vanita D Revankar (Wolters Kluwer Medknow Publications, 2017)
Enamel White spot lesions are early signs of demineralization under the intact enamel, which may or may not lead to the development of caries. An inactive white spot lesion might act as an arrested dental caries and impair the esthetic appearance by displaying a milky white color from its interior opacity. The first choice of treatment is remineralization with various remineralizing agents such as fluoride and ACP-CCP. Caries infiltration is a less invasive and effective method for arresting the white spot lesions. It also improves the esthetics by masking the chalky white appearance by the process of optical adaptation to the adjacent healthy enamel. This is achieved by the hydrophobic resin, which has a similar refractive index to that of the healthy enamel.